Endemism in the mammalian fauna of the Carpathians - Barkasi, Z. (Праці теріологічної школи, 2016)
The paper presents a survey of the concept of endemism with special attention to the most actual problems of interpretation of this biogeographic phenomenon. The overview of the main processes that determine species richness in areas of endemism is presented as well. The unique biogeographic location of the Carpathian mountain system allows considering this region as a special area, where endemic elements are represented on such taxonomic levels as species and, especially, subspecies. Proposed here are 14 subspecies of mammals to consider them endemic for the Carpathian region and a brief overview of these subspecies is given as an annotated list. Substantiated here is the expediency to consider the Carpathian region a local biodiversity hotspot that requires increased attention for conservation, in particular because of significant number of isolated populations of highly specialized species. The loss of these taxa would mean not only a significant depletion of the local biodiversity, but also the loss of the region’s uniqueness in general. У праці представлено огляд концепції ендемізму, з особливою увагою на найбільш актуальні проблеми тлумачення цього біогеографічного феномену, а також основних процесів, що визначають видове різноманіття областей ендемізму. Унікальне біогеографічне розташування Карпатської гірської системи дозволяє розглядати цей регіон як особливу область, де ендемічні елементи представлені на рівні видів, а надто підвидів. Запропоновано виділити 14 підвидів ссавців у якості ендемічних для цього регіону, також подано короткий огляд кожного з них у вигляді анотованого списку. Обґрунтовано доцільність розглядати Карпатський регіон як локальну «гарячу точку» біорізноманіття, що потребує посиленої уваги природоохоронців, зокрема через наявність значної кількості ізольованих популяцій вузькоспеціалізованих видів. Втрата цих таксонів означатиме значне збіднення локального біорізноманіття і втрати унікальності регіону загалом.